The transcription factor PPARα is overexpressed and is associated with a favourable prognosis in IDH‐wildtype primary glioblastoma. Issue 7 (23rd March 2017) - Haynes, Harry R; White, Paul; Hares, Kelly M; Redondo, Juliana; Kemp, Kevin C; Singleton, William G B; Killick‐Cole, Clare L; Stevens, Jonathan R; Garadi, Krishnakumar; Guglani, Sam; Wilkins, Alastair; Kurian, Kathreena M
Abstract : Aims: PPARα agonists are in current clinical use as hypolipidaemic agents and show significant antineoplastic effects in human glioblastoma models. To date however, the expression of PPARα in large‐scale glioblastoma datasets has not been examined. We aimed to investigate the expression of the transcription factor PPARα in primary glioblastoma, the relationship between PPARα expression and patients' clinicopathological features and other molecular markers associated with gliomagenesis. Methods and results: With protein immunoblotting techniques and reverse transcription quantitative real‐time PCR, PPARα was found to be significantly overexpressed in glioblastoma compared with control brain tissue ( P = 0.032 and P = 0.005). PPARA gene expression was found to be enriched in the classical glioblastoma subtype within The Cancer Genome Atlas (TCGA) dataset. Although not associated with overall survival when assessed by immunohistochemistry, cross‐validation with the TCGA dataset and multivariate analyses identified PPARA gene expression as an independent prognostic marker for overall survival ( P = 0.042). Finally, hierarchical clustering revealed novel, significant associations between high PPARA expression and a putative set of glioblastoma molecular mediators including EMX2, AQP4, and NTRK2 . Conclusions: PPARα is overexpressed in primary glioblastoma and high PPARA expression functions as an independent prognostic marker in the glioblastoma TCGA dataset. Further studies are required to explore genetic associations with high PPARA expression and to analyse the predictive role of PPARα expression in glioblastoma models in response to PPARα agonists.